Approximate Quartic and Quadratic Mappings in Quasi-Banach Spaces - M. Eshaghi Gordji; H. Khodaei; Hark-Mahn Kim (International Journal of Mathematics and Mathematical Sciences)
we establish the general solution for a mixed type functional equation of aquartic and a quadratic mapping in linear spaces. In addition, we investigate the generalized Hyers-Ulam stability in p-Banach spaces.